2023
DOI: 10.5194/essd-15-2223-2023
|View full text |Cite
|
Sign up to set email alerts
|

RC4USCoast: a river chemistry dataset for regional ocean model applications in the US East Coast, Gulf of Mexico, and US West Coast

Abstract: Abstract. A historical dataset of river chemistry and discharge is presented for 140 monitoring sites along the US East Coast, the Gulf of Mexico, and the US West Coast from 1950 to 2022. The dataset, referred to here as River Chemistry for the U.S. Coast (RC4USCoast), is mostly derived from the Water Quality Database of the US Geological Survey (USGS) but also includes river discharge from the USGS's Surface-Water Monthly Statistics for the Nation and the U.S. Army Corps of Engineers. RC4USCoast provides mont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Our analysis of the USGS‐derived river chemistry revealed an important temporal variability in Alk and DIC from the MARS, which is inversely related to river discharge. This flow‐dependent pattern is a common feature in many riverine systems, associated with the dilution of major river's solutes during high‐discharge periods (Gomez et al., 2023; Joesoef et al., 2017; Li et al., 2022). The seasonal changes in MARS's carbonate chemistry decreased both Alk and DIC during winter‐spring, and increased it during summer‐fall.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our analysis of the USGS‐derived river chemistry revealed an important temporal variability in Alk and DIC from the MARS, which is inversely related to river discharge. This flow‐dependent pattern is a common feature in many riverine systems, associated with the dilution of major river's solutes during high‐discharge periods (Gomez et al., 2023; Joesoef et al., 2017; Li et al., 2022). The seasonal changes in MARS's carbonate chemistry decreased both Alk and DIC during winter‐spring, and increased it during summer‐fall.…”
Section: Discussionmentioning
confidence: 99%
“…In the northern GoM shelf, river inputs are largely dominated by the MARS signature, but small rivers can also play a significant role as drivers of Ω Ar variability at a more local level (estuaries, bays). The system could be especially sensitive to rivers along the states of Mississippi and Alabama (east of the MARS delta), as those are characterized by much lower Alk:DIC ratios than the MARS (Gomez et al., 2023), which would negatively impact Ω Ar . It has been shown that El Nino‐Southern Oscillation (ENSO) influences the MARS discharge during winter, as well as discharges from other northern GoM rivers during winter‐spring, with El Niño periods associated with increased river flow and La Niña periods with decreased river flow (e.g., Gomez et al., 2019; Tootle et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The associated export of organic carbon to the bottom layer and its remineralization decreases dissolved oxygen (DO) and releases CO 2 , promoting bottom hypoxia and acidification during summer, when a strong stratification prevents vertical mixing of the whole water column (Cai et al, 2011;Rabalais et al, 2007). Besides these biologically induced changes, the MARS has relatively high concentrations of total alkalinity (Alk) and DIC compared to other rivers in the United States (Gomez et al, 2023), which further influences ocean carbonate patterns. For example, high salinitynormalized alkalinity in the northern GoM has been connected to the mixing of alkalinity-rich waters from the MARS (Yang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%